Characteristics of positive and negative autobiographical memories central to identity: emotionality, vividness, rehearsal, rumination, and reflection - Pociunaite, Justina; Zimprich, Daniel (Frontiers in Psychology, 2023)
Introduction: Some events are remembered as more central to a person’s identity than others. However, it is not entirely clear what characterizes these autobiographical memories central to one’s identity. In this study, we examined the effects of various characteristics on centrality to identity of positive and negative memories. Characteristics such as emotionality, vividness, and how frequently a memory is retrieved and shared with others as well as ruminative and reflective self-foci were studied. Methods: The sample included 356 participants (18-92 years of age). First, participants responded to demographic questions and individual difference questionnaires. Next, they recalled memories in response to 12 emotional cue words. The cue words were balanced for emotional valence (i.e., six positive and six negative) and presented in a random order. After retrieving all memories, participants rated them regarding centrality, using the short seven-item Centrality of Event Scale and other memory characteristics, on a seven-point Likert scale. Multivariate multilevel regression was used for data analyses, to consider multiple characteristics at the same time and account for data dependency within individual. Results: The results showed that emotionality, vividness, and frequency of memory retrieval contributed to higher centrality of memories, and employing a reflective self-focus resulted in rating memories as more central. In specific cases, these characteristics were associated differently with centrality of positive and negative memories. Discussion: Central memories can be perceived as markers in a person’s life story. The findings of this study suggest that these marker events are also highly available in a person’s memory system, by being actively emotional, visually rich, and frequently retrieved. Moreover, not only memory characteristics but also individual’s features are important to fully understand the autobiographical memory centrality.